The Effect of Executive Compensation, Executive Characteristics, An Executive Shareholding on Tax Avoidance - Nabila Qotrunnada; Tjoa Han Hwa; Dwi Mayasari (Universitas Mercu Buana, 2023)
This study aims to empirically prove the effect of executive compensation, executive characteristics, and executive share ownership on tax evading. This study was showed in the consumer goods manufacturing corporation listed on the Indonesia Stock Exchange (IDX) from 2016–2020, using a descriptive associative research method and secondary data. The sampling method used purposive. This research used 16 sample corporations, with a five-year research period of 5 years, so 80 samples were obtained for data processing using Microsoft Excel and the e-View Statistical software applications to analyze descriptive statistics, model conformity tests, classical assumption tests, coefficients of determination (R2), linear regression analysis of panel data, statistical test F and statistical test t. Results of statistical test F executive-compensation variables, executive-characteristics, and decision-making-shareholdings affect tax avoidance. The statistical test t of the executive compensation variable partially has a optimistic and significant effect on dividend payments—however, the executive's variable characteristics and the executive shares' ownership harm tax evading.